Pengaruh Electronic Word-of-Mouth (e-WOM) melalui Media Sosial TikTok terhadap Purchase Intention pada Produk Skintific - Diana Fajarwati; Tarisya Oktavia Cahya (Lembaga Yasin AlSys, 2025)
Short-form video-based social media platforms such as TikTok have become primary channels for the dissemination of electronic word-of-mouth (e-WOM), significantly influencing consumer behavior. However, research gaps remain regarding the roles of information quality, quantity, credibility, and consumer attitudes in shaping purchase intention. This study aims to analyze the impact of e-WOM on TikTok on the purchase intention of Skintific products by applying the Information Acceptance Model (IACM). Data were collected from 186 respondents selected through purposive sampling, based on the criteria of being TikTok users aged 18 or older who had accessed Skintific product reviews. The research instrument was an online questionnaire using a five-point Likert scale, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS software. The results indicate that Information Quality, Information Credibility, and Attitude Towards Information have a positive and significant effect on Information Usefulness, whereas Information Quantity does not show a significant effect. Furthermore, Information Usefulness has a positive and significant influence on Information Adoption, which in turn significantly affects Purchase Intention. These findings highlight that quality, credibility, and consumer attitude toward information are key determinants in enhancing purchase intention through e-WOM, while the quantity of information is not always relevant within the context of TikTok as a short-form video platform.